Ventriculoperitoneal shunt malfunction caused by fractures and disconnections over 10 years of follow-up - Erol, Fatih Serhat; Ozturk, Sait; Akgun, Bekir; Kaplan, Metin (Springer, 2017)
Purpose We have discussed the diagnosis and treatment approaches in patients with discontinued (disconnected or fractured) ventriculoperitoneal (VP) shunts that caused mechanical dysfunction. Methods Between 2006 and 2016, VP shunt surgery was performed on 1357 pediatric patients in our clinic. In follow-up examinations, we retrospectively reviewed patients who underwent revision surgery. Except for diagnosis of discontinued VP shunt, by excluding revision-surgery patients, only those patients who underwent surgical treatment owing to discontinued (fracture or disconnection) catheter were included in the study. Age at first surgery, sex, reason for shunt discontinuity, anatomical region of pathology, time to discontinuity diagnosis after first surgery, and presence or absence of symptoms were evaluated. Results One thousand three hundred fifty-seven VP shunt surgeries were performed in total, with 305 (22.4%) patients requiring revision surgery. Of these 305 patients, after accounting for other complications like obstruction, infection, overdrainage, and so on, 25 (8.1%) patients (14 male, 11 female) required re-surgery due to discontinuity. The mean age of these patients was 5.4 +/- 2.1 months during the first VP shunt surgery, and the mean age during revision surgery was 71.7 months. The mean duration until discontinuity was diagnosed was 66.3 +/- 24.1 months (76.1 months for catheter fractures and 45.6 months for disconnections (p 0.021)). Conclusion Disconnection and fracture are two significant mechanical VP shunt dysfunctions and must be adequately researched and understood even during routine follow-ups. A disconnected or fractured shunt may be working and it is not safe to state that the shunt is no longer needed.
Keywords: Hydrocephalus; Ventriculoperitoneal shunt; Fracture; Disconnection; Complication